SOCIAL BENEFITS OF THE FOREST - Seling, Irene (1999)
In the present work the methods for evaluating the social benefits of the forest are introduced. After discussions about the definition, the differences between the nations and the characteristics of the social benefits, the fundamental problems of evaluation and the advantages and disadvantages of the diferent methods are described. The last part deals with the present subsidies and context problems, adopted in Germany, in forest production.